#TITLE_ALTERNATIVE# - HARIS WATONI (NIM 30503006), ABDUL
The fast development and application of voltammetry methods contribute to the progress of both method and technique developments for conductive polymers synthesis. Cyclic voltammetry technique enable, electropolymerization mechanism and deposition of conductive polymers on the surface of electrode be controlled. The invention of conductive polymers accelerate the development of determination techniques of some ions, wich based on electrochemical reaction. Such polymers could be applied as ion sensor membranes. The development of conductive polymer as electrochemical sensor membrane for ions coated-wire electrodes have been studied intensively. However, there is still a problem of short life time and reproducibility for those electrodes. Consumption of anionic surfactants for industry and daily activities increases very fast. Thus, development of determination methods and techniques of anionic surfactants in aqueous sample solution is very important. Previously polyaniline coated Pt-wire as sodium dodecyl sulphate (SDS) sensor electrode has been fabricated. Electrode sensitivity towards dodecyl sulphate anion was approximately 59,0 mV/decade. However, electrode's selectivity towards other anions was not reported. Apart from that, polyaniline deposition on the electrode's surface was not efficient. To obtain optimum sensitivity of such electrode, it was necessary to scan for 400 cycles. Other researchers reported polypyrrole coated Pt-wire as sodium dodecylbenzene sulfonate (SDBS) sensor electrodes. The sensitivity and selectivity of the electrodes toward dodecyl benzena sulfonate (DBS negative) anion were very good, without potentiometric interferences of other inorganic and octyl sulfate anions. However, dodecyl sulphate and tetradecyl sulphate anions interfere DBS(-) analysis. In this research, the influence of conductivity and morphology of the polymeric membranes to potentiometric characteristics of SDS and SDBS sensor electrodes has not been elaborated yet. Such electrodes were prepared via electropolymerization reaction of pyrrole, using cyclic voltammetry technique in the solution containing a certain anionic surfactant ionophore and supporting electrolyte. Cyclic voltammetry parameters and electrodes performance were then evaluated. Cyclic voltammetry parameters, such as potential range and scan rate were optimized. On the other hand, to optimize the electrode's performance, electrode's sensitivity as the most important potentiometric characteristics, we are first evaluated. Optimum parameters to be determined were number of scanning cycles, pyrrole concentration, type and concentration of specific ionophore and also supporting electrolyte, conditioning systems of electrode, as well. A specific ionophore could be trapped in the matrix of the polypyrrole membrane during electropolymerization process. Different ionophore trapped in the polypyrrole membrane, different conductivity and morphology of the membranes. Polypyrrole membrane containing HDBS ionophore showed lower conductivity than the membrane containing HDS ionophore. The highest membrane conductivity was belong to polypyrrole membrane containing HOS ionophore. In the meanwhile, we observed the relationship among membraneÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â’s conductivity and morphology on the surface of Au-coated wire electrodes and electrode's performance, especially sensitivity and response time of the electrodes. It was found that there was a difference in potentiometric characteristics of the three kinds of electrodes (Au-PPy-DS, Au-PPy-OS, and Au-PPy-DBS). This fact could be an indication that it may be necessary to optimize each electrode parameters for each individual anion surfactant electrode. The success of the research will have an impact on the development of new material serving as membranes of electrochemical sensor. We propose to develop other surfactant sensors having good reproducibility and longer life time.